Using Ant colony optimization for solving 0-1 Knapsack problem - Ø´Ù…Ø®ÙŠ Ø¬Ø§Ø¨Ø±, Ø¹Ø¯Ù†Ø§Ù†; ØØ³Ù† Ù‡Ø§Ø¯ÙŠ, Ø¥ÙŠÙ…Ø§Ù† (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The (0-1)Knapsack problem of the difficult problem which does not possess the algorithm in parametric approximation as the complexity of this matter belongs to the problems of the type (NP-hard), the research using the algorithm of ant colony optimization (ACO) to solving the problem, and also generate a set of problems to determine the efficiency of the algorithm and compared with other methods of numerical results have proven the efficiency of the algorithm in comparison with other methods and also the time used to solving problem was standard compared to the other methods.